1999
DOI: 10.1017/s0952523899164058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the responses of AII amacrine cells in the dark- and light-adapted rabbit retina

Abstract: We studied the light-evoked responses of AII amacrine cells in the rabbit retina under dark- and light-adapted conditions. In contrast to the results of previous studies, we found that AII cells display robust responses to light over a 6-7 log unit intensity range, well beyond the operating range of rod photoreceptors. Under dark adaptation, AII cells showed an ON-center/OFF-surround receptive-field organization. The intensity-response profile of the center-mediated response component followed a dual-limbed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 57 publications
11
99
2
1
Order By: Relevance
“…Mills and Massey (1995) showed that larger biotinylated tracers pass rather poorly through gap junctions between AII amacrine cells and bipolar cells, whereas they pass easily through homotypic gap junctions between AII amacrine cells. However, tracer coupling seems to be bidirectional between AII amacrine and ON bipolar cells in rabbit retina (Trexler et al, 2001), in agreement with physiological data from Xin and Bloomfield (1999), who demonstrated that cone signals, presumably transmitted by means of the ON bipolar/AII amacrine cell gap junctions, can be measured in AII amacrine cells. Thus physiological data neither support nor contradict conclusively the possibility that Cx36 and Cx45 form the heterotypic gap junctions between AII amacrine and ON bipolar cells.…”
Section: Cx45 In the Rod Pathwaysupporting
confidence: 89%
“…Mills and Massey (1995) showed that larger biotinylated tracers pass rather poorly through gap junctions between AII amacrine cells and bipolar cells, whereas they pass easily through homotypic gap junctions between AII amacrine cells. However, tracer coupling seems to be bidirectional between AII amacrine and ON bipolar cells in rabbit retina (Trexler et al, 2001), in agreement with physiological data from Xin and Bloomfield (1999), who demonstrated that cone signals, presumably transmitted by means of the ON bipolar/AII amacrine cell gap junctions, can be measured in AII amacrine cells. Thus physiological data neither support nor contradict conclusively the possibility that Cx36 and Cx45 form the heterotypic gap junctions between AII amacrine and ON bipolar cells.…”
Section: Cx45 In the Rod Pathwaysupporting
confidence: 89%
“…At the EM level, the presynaptic elements are ribbon synapses here as well. Although it has not been examined extensively, electrophysiological recordings suggest that the input is mediated by iGluRs (Veruki et al, 2003; see also Xin and Bloomfield, 1999). The AII amacrine lobular appendages can also be presynaptic to the axon terminals of OFFcone bipolar cells from which they receive input and to dendrites of OFF-ganglion cells (McGuire et al, 1984;Strettoi et al, 1992Strettoi et al, , 1994Tsukamoto et al, 2001).…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%
“…It is well known that retinal gap junctions are modulated by light and dark adaptation (Dong and McReynolds, 1991;Xin and Bloomfield, 1999). Thus, we investigated the effects of light and dark adaptation on the properties of the electrically coupled Mb1-BC network.…”
Section: Effects Of Light and Dark Adaptationmentioning
confidence: 99%